Nauczyciel w pedagogice planu daltońskiego - Kwella, Marta (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
The article is aimed to answer the questions: Who is Dalton teacher? What are the characteristics of Dalton teacher? What she/ he should know and focus on? What method of working with children should she/he incorporate to develop their skills in three basic areas: responsibility, independency and cooperation? Basing on literaturę data and my own experience I will try to describe Dalton method teacher and his/her method working with children. Dalton plan isn’t neither rigid nor dogmatic, as described by its creator Helen Parkhurst. Through analysis of Dalton plan’s fundamental characteristics. I will present the profile of its teacher, keepeing in mind that Parkurst herself was very flexible.